Age and organizational identification: empirical findings from professional sports. Issue 10 (2nd July 2016) - Bergmann, Andreas; Schmidt, Sascha L.; Schreyer, Dominik; Torgler, Benno
ABSTRACT: Although identification is critical to organizational survival, knowledge on how identification changes and evolves over time is still limited. Not only can tastes and choices vary across both social context and time, but individuals can change or choose their identity, as well as their ideals, group loyalty and/or social category. Hence, in this letter, we examine the relation between organizational identification and age using five large sports consumer surveys as a snapshot of the age distribution of team identification. Our results provide evidence of robust U-shaped age profiles, with a probable turning point in the 40s.